Successful treatment of isolated bile leakage after hepatectomy combination therapy with percutaneous transhepatic portal embolization and bile duct ablation with ethanol: a case report - Norio Kubo; Norifumi Harimoto; Kei Shibuya; Norihiro Ishii; Mariko Tsukagoshi; Takamichi Igarashi; Akira Watanabe; Kenichiro Araki; Masaya Miyazaki; Hiroyuki Kuwano; Ken Shirabe (Surgical Case Reports)
Abstract Background Bile leakage after hepatectomy still causes relatively serious problems, and some types of bile leakage are intractable. Case presentation We report a case of postoperative isolated bile duct leakage managed successfully by combination therapy of percutaneous transhepatic portal vein embolization (PTPE) and bile duct ablation with ethanol. A 61-year-old man diagnosed with hepatocellular carcinoma underwent partial hepatectomy. On postoperative day 1, bile leakage was detected at the drainage tube. Simple drainage treatment did not improve the situation. He was diagnosed with isolated bile leakage based on fistulogram from the drainage tube that showed the bile duct at segments V and VIII but not the common bile duct. A volume of drainage fluid of 200 mL/day was observed. Combination therapy with PTPE and bile duct ablation with ethanol was planned. After the percutaneous transhepatic cholangiography, the drainage tube was inserted into the bile duct, and PTPE was performed to segments V and VIII. The amount of drainage fluid decreased, and bile duct ablation with ethanol was performed to the isolated bile duct. No complication was found following combination therapy. Conclusion In this case, we successfully treated a patient with isolated bile leakage by combination therapy with PTPE and bile duct ablation.